Activating dormant strongyloidiasis secondary to COVID-19 treatment - Fahad Alkaabba; Holman Li; Farrah Ibrahim (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
The SARS-CoV-2 pandemic has grown into a major global concern with huge efforts to combat the spread. Exaggerated inflammatory response plays a major role in which was the rationale to use corticosteroids to treat patients. However, multiple studies showed an association between opportunistic and bacterial infections with corticosteroid therapy. We report a case of a 76 year old patient diagnosed with COVID-19 treated with 10 days Dexamethasone and Remdesivir who presented with abdominal symptoms with eosinophilia. Biopsy and stool studies revealed Strongyloides stercoralis larvae. The patient was treated with 2 doses of Ivermectin with significant clinical resolution. Clinician should have high clinical suspicion for Strongloydiasis in patients who have lived or visited endemic areas and for patients with unexplained eosinophilia. Prompt treatment with Ivermectin is crucial for confirmed cases and high risk cases where obtaining a diagnosis is unfeasible.